Nutrient Intake and Phytate-to-Zinc Molar Ratio among Stunted and Non-Stunted Children in Malang City - Willyanti, Wardah; Riyadi, Hadi; Nasution, Zuraidah (Universitas Airlangga, 2024)
Stunted is a condition of malnutrition caused by inadequate nutrient intake, especially in protein and zinc. Zinc deficiency can lead to impaired growth and increased risk of infectious disease due to inadequate zinc intake and low bioavailability of zinc in food. The purpose of this research was to analyze the nutrient intake and phytate-to-zinc molar ratio in children. This research was an analytical observational study with cross-sectional design. Children aged 6-59 months with stunted (n=61) and non-stunted (n=65) nutritional status were chosen by stratified random sampling in Ciptomulyo Health Center, Malang city. Nutrient and phytate intake were taken using 2x24 hour food recall method, while zinc bioavailability was calculated using phytate-to-zinc molar ratio. The difference of independent variables were analyzed using Independent t-test and Mann Whitney test. The result of this study showed that there were significantly different energy and protein adequacy levels (p=0.018; p=0.001) and phytate intake (p=0.016) among stunted and non-stunted children. On the other hand, fat, carbohydrate, and zinc adequacy level did not show any significant differences. Furthermore, there were no significant difference in phytate-to-zinc molar ratio in the two group (p=0.158) with more than half children had high phytate-to-zinc molar ratio category. In conclusion, the stunted and non-stunted children showed significant differences in energy, protein, and phytate intake, while their zinc intake was not significantly different resulting in similar phytate-to-zinc molar ratio between both groups. This study show that sufficient intake of zinc can help to lower phytate-to-zinc molar ratio regardless of nutritional status of children.